2010
DOI: 10.1007/s10764-010-9416-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seasonal Folivory and Frugivory on Ranging Patterns in Rhinopithecus roxellana

Abstract: The distribution of food resources in time and space may affect the diet, ranging pattern, and social organization of primates. We studied variation in ranging patterns in a group of Sichuan snub-nosed monkeys (Rhinopithecus roxellana) over winter and summer in response to variation in their diet in the Qingmuchuan Nature Reserve, China. There was a clear diet shift from highly folivorous in winter to highly frugivorous in summer. The home range was 8.09 km 2 in summer and 7.43 km 2 in winter, calculated via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 48 publications
2
20
0
1
Order By: Relevance
“…For example, Kirkpatrick et al [43] and Liu et al [44] found that R. bieti had a larger home range during summer and traveled further each day when preferred foods were available. Our results are also consistent with studies of R. roxellana which report that DTL increases significantly in autumn and summer when food available is high [45][46][47]. This study supports the hypothesis that both the amount of travel required to find fruits and the time and energy available for traveling increase as the fruits in the diet increase [48].…”
Section: Seasonal Variability In Ranging Patternsupporting
confidence: 92%
“…For example, Kirkpatrick et al [43] and Liu et al [44] found that R. bieti had a larger home range during summer and traveled further each day when preferred foods were available. Our results are also consistent with studies of R. roxellana which report that DTL increases significantly in autumn and summer when food available is high [45][46][47]. This study supports the hypothesis that both the amount of travel required to find fruits and the time and energy available for traveling increase as the fruits in the diet increase [48].…”
Section: Seasonal Variability In Ranging Patternsupporting
confidence: 92%
“…Here, travel distances are bimodal in winter but not in summer. 32 This is to be expected if range use is driven by the nature of food resources, which will differ as diets change over the seasons.…”
Section: Daily Travel Distancementioning
confidence: 99%
“…that live in temperate, mountainous regions in China [Kirkpatrick and Long, 1994;Kirkpatrick et al, 1998;Tan et al, 2007;Li et al, 2008;Zhong et al, 2008;Li et al, 2010]. Snub-nosed monkeys are members of the subfamily Colobinae or 'leaf-eating monkeys'.…”
Section: Introductionmentioning
confidence: 99%
“…nov. at 1,400-3,400 and 1,720-3,190 m, respectively, in temperate mixed deciduous broadleaf and conifer forest and R. bieti at 2,600-4,600 m in temperate mixed forest dominated by fir [Kirkpatrick, 1998;Yang et al, 2002;Tan et al, 2007;Li et al, 2008;Grueter et al, 2009;Geissmann et al, 2011;Kirkpatrick and Grueter, 2010;Li et al, 2010]. Regarding al-titudinal ranging, it has been suggested that R. bieti and R. roxellana adjust their movements in relation to food availability, human activities and climate [Hu et al, 1980;Zhao et al, 1988;Kirkpatrick and Long, 1994;Kirkpatrick et al, 1998;Su et al, 1998;Yang, 2003;Liu et al, 2004;Tan et al, 2007;Li et al, 2008;Zhong et al, 2008].…”
Section: Introductionmentioning
confidence: 99%